Phrenic nerve conduction studies: normative data and technical aspects - Maranhão, Analucia Abreu; Carvalho, Sonia Regina da Silva; Caetano, Marcelo Ribeiro; Alamy, Alexandre Hofke; Peixoto, Eduardo Mesquita; Filgueiras, Pedro Del Esporte Peçanha (Arquivos de Neuro-Psiquiatria, 2017)
Objective: The aim of the present study was to define normative data of phrenic nerve conduction parameters of a healthy population.Methods: Phrenic nerve conduction studies were performed in 27 healthy volunteers.Results: The normative limits for expiratory phrenic nerve compound muscle action potential were: amplitude (0.47 mv - 0.83 mv), latency (5.74 ms - 7.10 ms), area (6.20 ms/mv - 7.20 ms/mv) and duration (18.30 ms - 20.96 ms). Inspiratory normative limits were: amplitude (0.67 mv - 1.11 mv), latency (5.90 ms - 6.34 ms), area (5.62 ms/mv - 6.72 ms/mv) and duration (13.77 ms - 15.37 ms).Conclusion: The best point of phrenic nerve stimulus in the neck varies among individuals between the medial and lateral border of the clavicular head of the sternocleidomastoid muscle and stimulation of both sites, then choosing the best phrenic nerve response, seems to be the appropriate procedure.
Keywords: electrodiagnosis; reference values; phrenic nerve; spirometry; neural conduction